Risk Factors Associated with Early Onset Group B Streptococcal Disease and Newborn Outcomes in a Tertiary Care Center in Pakistan - Muhammad Naveed Khani, Sohail Salat, Shabina Ariff, Amir Afzal, Saeed Ahmed, Muhammad Usman (Pakistan Journal of Medical & Health Sciences, 2023)
Background: To assess the risk factors associated with early onset group B streptococcal disease and newborn outcomes in a tertiary care center in Pakistan. Methods: A prospective cohort study design was implemented in the postnatal wards and neonatal intensive care unit of Aga Khan Hospital between 15 December 2021 – 15 June 2022. The exposed group included all pregnancies with risk of GBS infection, the un-exposed group included all pregnancies with no risk factors for GBS. All births were followed for outcomes during admission and after discharge for 28 days of life. Information about the mother and baby dyad was retrieved from the medical records. A second proforma was filled out at the time of discharge (2 to 5 days of life for healthy babies and at 10 to 15 days of life for babies admitted for NICU). These were the average length of stay of healthy and ill newborns at our facility.) The final follow up was at 28 days of life which was at the clinic or telephonic. Data on morbidities such as sepsis, use of antibiotics and hospitalization breast feeding practices was captured at the day 28 follow up. Results: A total of 78 patients were included, with a mean maternal age of 30.82 ± 4.65 years and gestational age of 37.26 ± 2.1 weeks. GBS colonization was positive in high vaginal swab in 23 (29.5%) patients, in urine culture in 16 (20.2%) patients, and 1 (1.3%) patient who delivered a previous baby with GBS infection. Two patients suffered from pneumonia among them one patient also had sepsis and 77 patients were stable at 28 days. In 16 (41%) cases of GBS colonization, high vaginal swab yielded a negative result. Similarly, in 23 (59%) patients with GBS colonization, urine culture was also negative. Only one patient with GBS colonization had a history of a previous infant with GBS infection. Approximately 70% of GBS positive had PROM. Maternal Leukocytosis and tachycardia were significantly higher in patients with GBS (p<0.0001). Uterine tenderness was found in 14 (35.9%) mothers with GBS colonization (p<0.0001). Intrapartum fever was significantly more common in mothers with GBS colonization (p=0.011). Tachycardia was significantly higher in neonates of mothers with GBS colonization (p=0.01). Need of oxygen was significantly higher in neonates with mothers having GBS colonization (p=0.002). Conclusion: In hindsight, GBS colonization and the early onset of Group B streptococcus infection is a public health issue in Pakistan that requires attention. Recommended antenatal screening measures should be implemented, as well as the necessary steps, such as an antibiotics treatment regimen following a positive GBS colonization report, to protect newborns from this disease. Keywords: colonization, maternal risk factors, group B streptococcal, early onset group B streptococcal disease, GBS, PROM